Glycemia Is Related to Impaired Cerebrovascular Autoregulation after Severe Pediatric Traumatic Brain Injury: A Retrospective Observational Study - Young, Adam M. H.; Adams, Hadie; Donnelly, Joseph; Guilfoyle, Mathew R.; Fernandes, Helen; Garnett, Mathew R.; Czosnyka, Marek; Smielewski, Peter; Plummer, Mark; Agrawal, Shruti; Hutchinson, Peter J. (Frontiers in Pediatrics, 2017)
Introduction: A strong association exists between hyperglycaemia and outcome in paediatric traumatic brain injury (TBI). Herein we describe observations of serum markers of glucose metabolism in a cohort of paediatric TBI patients and how these variables are related to parameters of intracranial pathophysiology. Methods: A retrospective analysis was performed on paediatric severe traumatic brain injury patients admitted to Addenbrookes Hospital Paediatric Intensive Care Unit (PICU) between January 2001 and December 2013. Demographic, outcome, systemic physiological, and cerebral autoregulatory data were extracted for patients who had received continuous invasive monitoring (ICM+, Cambridge Enterprise, Cambridge, UK). Data were analysed using a mixed linear model. Results: Forty-four patients with an average age of 12.2 years were admitted to the Paediatric Intensive Care Unit with a TBI requiring invasive neurosurgical monitoring. Thirty-two patients (73%) survived, with favourable outcomes in 62%. The mean (SD) intracranial pressure (ICP) was 17.6+9.0 mmHg, MAP was 89.7+9.0 mmHg and PRx was -0.01+0.23 a.u. The mean (SD) serum lactate was 2.2 (3.3) mmol/L. and the mean (SD) serum glucose was 6.1 (1.6) mmol/L. Early hyperglycaemia was strongly associated with both PRx (Pearson correlation 0.351, p <0.001) & ICP ((Pearson correlation 0.240, p = 0.002) death (p=0.021) and impaired cerebral autoregulation (p = 0.02). There was a strong association between ICP and serum lactate (p = 0.001). Conclusion: Increases in systemic glucose are associated with impaired cerebrovasular autoregulation after severe paediatric TBI. Moreover, deranged blood glucose is a marker of poor prognosis. Further studies are required to delineate putative mechanisms of hyperglycaemia induced cerebral harm.